Patient and Public Involvement (PPI) reporting in maternal and neonatal clinical trials: an exploratory review - Daly, Deirdre; Hannon, Kathleen; Smith, Valerie (My University, 2026)
Background: Patient and public involvement (PPI) is increasingly a research priority encouraged by health research funders. It is difficult to know, however, how prevalent PPI is within research. The aim of this review was to gain a contemporary understanding of the frequency and types of PPI being reported in maternal and neonatal clinical trial reports, and if an increase in PPI reporting was evident over time. Methods: An exploratory review of maternal and neonatal trial reports published in nine healthcare journals between 2017-2022 was undertaken. A search was conducted for eligible trial reports in each journal using SCOPUS, in addition to a manual search of each journal’s archive. Once an eligible trial report was identified, a search was conducted for the trial’s associated protocol. Both trial documents were reviewed for any information on PPI activity. Descriptive statistics of the included trials’ characteristics were produced. Results: Three-hundred and fifty-two trial reports and 162 associated trial protocols were identified and included in the analysis. Of these, 48 (14%) reported PPI, either within the main trial record (n=47) or solely in the trial protocol (n=1). Twenty (42%) of these trials were conducted in the UK. Thirty-four trials reported PPI contributors in trial design and planning, 31 trials reported PPI during the running of the trial and 20 trials involved contributors in trial analysis and dissemination. There was no sustained increase in PPI reporting over the included timeframe. Conclusions: There is minimal reporting of PPI in maternal and neonatal clinical trials, with wide variations in the depth of information provided. PPI reporting guidelines in academic journals may be beneficial in prompting researchers to provide PPI information and to raise awareness of the profile of PPI in maternal and neonatal trial research.
PUBLISHED
Keywords: Patient and public involvement; neonatal trials; maternal trials; GRIPP2 checklist; clinical trials methodology; Maternity Care; NEONATOLOGY; Primary care